(untitled) - Farnsworth, Steven Robert (Hoboken, NJ, 2010)
A step-by-step guide to help you master the commonly used yet complex task of welding. Takes you from material evaluation all the way through the welding process.
Understanding welding basics -- Welding on a budget: stick and tig welding -- Discovering mig welding -- Getting fancy: plasma cutting, oxyfuel cutting, and other processes -- Putting welding into action with projects and repairs -- The part of tens.
Keywords: Welding; Handbooks, manuals, etc